2022
DOI: 10.3390/diagnostics12102400
|View full text |Cite
|
Sign up to set email alerts
|

Inter/Intra-Observer Agreement in Video-Capsule Endoscopy: Are We Getting It All Wrong? A Systematic Review and Meta-Analysis

Abstract: Video-capsule endoscopy (VCE) reading is a time- and energy-consuming task. Agreement on findings between readers (either different or the same) is a crucial point for increasing performance and providing valid reports. The aim of this systematic review with meta-analysis is to provide an evaluation of inter/intra-observer agreement in VCE reading. A systematic literature search in PubMed, Embase and Web of Science was performed throughout September 2022. The degree of observer agreement, expressed with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…Another issue relevant to the diagnostic performance of SBCE is interobserver agreement on detection rate and finding classification. A recent metanalysis 21 found that the overall pooled estimates for “perfect” or “good” interobserver and intra-observer agreement were only 23% and 37%, respectively. The reader's experience, accumulating fatigue, and lack of standardization in describing small bowel lesions could affect the interobserver bias 22 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Another issue relevant to the diagnostic performance of SBCE is interobserver agreement on detection rate and finding classification. A recent metanalysis 21 found that the overall pooled estimates for “perfect” or “good” interobserver and intra-observer agreement were only 23% and 37%, respectively. The reader's experience, accumulating fatigue, and lack of standardization in describing small bowel lesions could affect the interobserver bias 22 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, although it has been recently shown that CCE is well tolerated, safe, and can reduce the proportion of patients requiring CC [49], another meta-analysis has demonstrated that both bowel cleanliness and complete transit of CCE are insufficient as compared to CC [50]. In addition, it must be acknowledged that a systematic review has demonstrated that the inter/intra-observer agreement of capsule endoscopy is suboptimal, possibly due to heterogeneity in Country, capsule type, and bowel cleansing scale among included studies [51]. In this regard, it has been shown that the use of prucalopride can increase the proportion of patients with complete colon capsule transit and acceptable preparation [52].…”
Section: Non-invasive and Minimally Invasive Alternatives To Conventi...mentioning
confidence: 99%
“…However, these judgments tend to be subjective. During colonoscopy, when a gastroenterologist evaluates bowel preparation quality, many instruments, such as the aronchick bowel preparation scale, Boston bowel preparation scale, Ottawa bowel preparation scale, and Chicago bowel preparation scale, are used to reach an objective judgment, [ 6 , 7 ] however, those are still subjective. With the Boston bowel preparation scale, gastrointestinal endoscopists familiarize themselves with photographs of objective indicators of varying degrees of bowel cleanliness and attempt to perform an objective evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] However, even if gastroenterologists attempt to establish objective standards, interobserver reliability is diverse and judgments may differ among evaluators. [ 6 , 7 ] Moreover, there has been much less research in the field of CE. Evaluation of the intestinal preparation in CE is mainly performed by setting the visible range of the mucosa.…”
Section: Introductionmentioning
confidence: 99%